Transformative conversations about sexualities pedagogy and the experience of sexual knowing - Trimble, Lisa (Sex Education : Sexuality, Society and Learning, 2009)
One of the hallmarks of sex education traditionally has been its Cartesian endorsement of mind/body dualism; we have preferred to equate ‘self’ as synonymous with ‘mind’, and have invested heavily in believing in the valence of rationality‐based sexualities education. We generally do not consider the way ‘self’ negotiates, interprets and relates to sexual knowledge in all of our complexity, including our messy, embodied and emotional lives. In this paper I address what I think are several much‐needed conversations for a holistic pedagogy of sexualities to incorporate, including the falseness of the mind/body split, reconsidering what counts as sexual knowledge, the role of the performative in communicating our sexual knowing, and the importance of considering affect in learning about sexualities. The second part of the paper examines pedagogical considerations currently absent in dialogues of sexualities education, such as incorporating transformational learning strategies in teaching sexualities, and what it means to educate toward being a sexual citizen. Finally, I will outline how discussions of epistephenomenology (our relationship to and how we experience knowledge) can contribute to moving toward a vision of a critical, cultural sexualities education.
Keywords: approches et analyses; corps; discipline; discours dominant; phénoménologie; ressource en ligne; savoir expérientiel; science de l'éducation; sciences humaines; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; émotions; épistémologie

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques